PENANGANAN PENYAKIT BEBAINAN (GANGGUAN DISOSIATIF) DALAM ANALISIS SEMIOTIKA - Brahmandika, Pande Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The aim of this research is to describe the form, function and meaning of treatment for bebainan disease. This research uses the theory of semiotic analysis. The method used is a qualitative method. The instruments used in this research were interviews, observation, in-depth literature study of informants. Determining informants used purposive sampling techniques. The results of this research are: first, treatment/cure for bebai disease, based on stories he has heard that bebai is made from various kinds of ingredients, including from the scrapes of dead babies, from the blood of people who died in accidents, there are also those who use ingredients from animals such as parts. certain of the horses so that they become jaran guyang, there are those who use white cloth which is tattooed in the form of rangda decorated with basic letters. Second, Tamba or serana is one unit as a tool that heals sick people, both support each other so that it can function optimally as a treatment